"Everyone Knows It's About Something Else, Way Down": Boredom, Nihilism, and the Search for Meaning in David Foster Wallace's The Pale King. Issue 3 (27th May 2017) - Goeke, Joseph F.
ABSTRACT: This article investigates the "something else" that underlies information-age boredom, according to The Pale King 's "Author, " and analyzes the novel's representations of boredom to that end. Wallace's decade-long engagement with the problem of boredom, which ended with his suicide, and The Pale King 's longest section, the story of "Irrelevant" Chris Fogle, are read in context with existentialist philosophies, particularly Viktor Frankl's and Albert Camus's contrasting treatments of boredom in Man's Search for Meaning and The Myth of Sisyphus, respectively. The "something" behind Fogle's boredom appears in this light as an aimless, default, self-centered nihilism, which he overcomes temporarily by choosing to see meaning in a job that others might view as absurd: working for the IRS. The article concludes by noting that Fogle's story and The Pale King in general significantly resist closed interpretation due to the open-endedness of Fogle's narrative, his ongoing drug dependency, and the recursive overall structure of Wallace's unfinished novel.